Evaluation of shear bond strength of different treatments of ceramic bracket surfaces - Andrade,Patrícia Helou Ramos (2012)
OBJECTIVE: To evaluate the bonding strength of the ceramic bracket and composite resin restoration interface, using four types of treatment on the base of the bracket. METHODOLOGY: 48 photoactivated composite resin discs were used (FiltekTM Z250) contained in specimens and divided into 4 groups of 12 specimens for each group according to the type of treatment performed on the base of the brackets. Once the brackets were bonded, the specimens were subjected to shear stress carried out in a universal testing machine (MTS: 810 Material Test System) calibrated with a fixed speed of 0.5 mm / minute. The values obtained were recorded and compared by means of appropriate statistical tests - analysis of variance and then Tukey's test. RESULTS AND CONCLUSIONS: The surfaces of ceramic brackets conditioned with 10% hydrofluoric acid for 1 minute, followed by aluminum oxide blasting, 50µ, after silane application and primer application, was considered the best method to prepare surfaces of ceramic brackets prior to orthodontic esthetic bonding.